A Socio-semantic analysis of Slang in Bruno Mars’ Song Lyrics - Muskitta, Jeanet Elisabet; Maruanaya, Hendrik Jacob (Koli Journal : English Language Education, 2021)
Song has been used as a pedagogical tool for different purposes in the EFL classroom. Song lyrics mostly tell the story of an artist's life using a variety of language styles. This study analyzed the lexical and contextual meaning of slang words used in Bruno Mars's song lyrics. Three lyrics from Grenade, Lazy Song, and Runaway Baby song titles were selected to identify slang words based on their construction includes the social meaning embedded in the lyric. The result indicated twenty-eight slang words that fall into the category of blending, clipping, acronym, coinage, and compounding. Coinage, the dominant characteristic of slang, relates to the association made with an object to create new meaning. Slang words compose of blending and clipping are understood in the lyrics, but acronyms, coinages, and compounding need contextual interpretation. The social meaning of all the slang words identified from the three lyrics is to express feelings and emotions about love, power, painfulness, and humiliation.